On the role of resonances in photoionization of metal clusters - Wopperer, P.; Dinh, P. M.; Reinhard, Paul-Gerhard; Suraud, E. (Journal of Physics: Conference Series, 2013)
We analyze electron emission from irradiated clusters by means of time-dependent density-functional theory (TDDFT) in real time. We focus on photo-electron spectra (PES) which deliver an invaluable tool to explore static and dynamical properties of irradiated species. We discuss, in particular, the role of resonances in the PES once the laser frequency is below the emission threshold which implies multiphoton processes. We show that the resonances in the electronic spectrum lead to the occurrence of several peaks in the PES and also strongly affect the standard scaling relations between ionization and the number of required photons for electronic emission.
CRIS-Team Scopus Importer:2023-07-24